Parents’ Attitudes towards Including Sexual Education Concepts in the School Curricula - Ighemine, Nadira; boutafnouchat, hamida; djouaibia, meriem (Dirasat: Educational Sciences, 2022)
Objectives: This article aims to reveal the attitudes of parents towards the inclusion of sexual education concepts in school curricula. Families and fathers play an essential role in shaping key aspects of their children’s gender identity and their sexual and social relationships. In addition, the involvement of parents in sex education increases its impact and sustainability, so it is necessary for any school that aspires to apply sex education to students to establish close cooperation with parents, and to find out the parents’ attitudes towards including the concepts of sex education in the curriculum. Methods: To achieve the goal of the study, a descriptive approach was used, by designing a questionnaire, which was applied to a sample of 100 fathers and mothers residing in the city of Guelma. Results: The results concluded that parents’ attitudes towards including sexual education concepts in school curricula are positive. There were no statistically significant differences in these trends due to the variables of gender and educational level.